Coulomb fission in multiply charged molecular clusters: experiment and theory - Harris, Christopher; Baptiste, Joshua; Lindgren, Eric B.; Besley, Elena; Stace, Anthony J. (American Institute of Physics, 2017)
A series of three multiply charged molecular clusters, (C6H6)nz+ (benzene), (CH3CN)nz+ (acetonitrile), and (C4H8O)nz+ (tetrahydrofuran), where the charge z is either 3 or 4, have been studied for the purpose of identifying patterns of behaviour close to the charge instability limit. Experiments show that on a time scale of ~10-4 s, ions close to the limit undergo Coulomb fission where all of the observed pathways exhibit considerable asymmetry in the sizes of the charged fragments, and are associated with kinetic (ejection) energies of between 1.4 and 2.2 eV. Accurate kinetic energies have been determined through a computer simulation of peak profiles recorded in the experiments and the results modelled using a theory formulated to describe how charged particles of dielectric materials interact with one another (Bichoutskaia et al. J. Chem. Phys. 2010, 133, 024105). The calculated electrostatic interaction energy between separating fragments gives an accurate account for the measured kinetic energies and also supports the conclusion that +4 ions fragment into +3 and +1 products as opposed to the alternative of two +2 fragments. This close match between theory and experiment supports the assumption that a significant fraction of excess charge resides on the surfaces of the fragment ions. It is proposed that the high degree of asymmetry seen in the fragmentation patterns of the multiply charged clusters is due, in part, to limits imposed by the time window during which observations are made.